EOR mechanism of fracture oil displacement agent for ultra-low permeability reservoir - Sunan Cong; Jierui Li; Weidong Liu; Yu Shi; Yalong Li; Kai Zheng; Xun Luo; Wenbo Luo (Energy Reports, 2023)
Due to the low permeability, small pore throat, and poor pore connectivity of ultra-low permeability reservoirs, fracturing was required to improve the flow environment of oil in the reservoir during its development. The combination of fracturing and oil displacement could reduce the complexity of the development of ultra-low permeability reservoirs. It was feasible to synthesize new surfactants to prepare fracturing oil displacement agents, but the research and development of new surfactants were difficult and costly. This paper aimed to experimentally investigate the imbibition displacement mechanism of fracturing flooding by combining the surfactant of chemical flooding with the fracturing fluid. With the conditions of the ultra-low permeability reservoir in block Y of Changqing Oilfield, the mechanism of remaining oil start-up and fractured oil displacement agent enhanced oil recovery in the ultra-low permeability reservoir was studied by microfluidic model experiment and NMR experiment. A mixture of fracture oil displacement agents was obtained by mixing heavy alkyl benzene sulfonate surfactant, a nonionic surfactant, and a betaine-type amphoteric surfactant. HAS-6C, HAS-5E, and HAS-5G were selected for their interfacial tension reaching 10−3 mN/m. Oil–water​ interfacial tension of HAS-5E was the lowest, which can be reduced to 10−4 mN/m. The ability to alter the wettability of HAS-6C was the most significant, which could make the contact angle go down to 64.5°. The multi-round dynamic and static imbibition experiments showed that the combination of selected surfactant and slickwater can greatly improve the imbibition recovery, of which HAS-6C could enhance oil recovery by 17%. The HAS-5E system with the lowest interfacial tension had the best effect of starting clustered residual oil, and the clustered residual oil saturation was reduced by 48.8%. The HAS-6C system with stronger wettability had the best effect of starting throat-like residual oil, and the throat-like residual saturation was reduced by 10.8%.